Air in gallbladder: Emphysematous cholecystitis or else? - Konstantinos Sitaridis; Iliana Domi; Maria Nathanailidou; George Chatzigiannis; Konstantinos A. Boulas; Gionous Sourtse; Anestis Hatzigeorgiadis (Clinical Case Reports)
Abstract Gas in gallstones represents a rare but well described radiological finding. Other causes of gas in gallbladder include biliary‐enteric fistula, sphincterotomy, gas forming organisms cholangitis. However, gas in gallbladder raises suspicion of emphysematous cholecystitis which necessitates prompt diagnosis and management due to its rapid clinical course and high mortality rate.